Effect of sodium dialysate variation in combining with ultra filtration on intradialytic hypotension and intradialytic weight gain for patients on hemodialysis - Mansour Ghafourifard; Mohsen Rafieian; Nahid Shahgholian; Mojgan Mortazavi (Journal of Mazandaran University of Medical Sciences, 2009)
(Received 24 December, 2009 ; Accepted 9 November, 2009)AbstractBackground and purpose: Intradialytic hypotension (IDH) is the most frequent complication in patients receiving haemodialysis (HD) that poses most problems for patient and treatment team. The use of sodium profile and ultra filtration (UF) profile is one of the preventive methods that have been recently introduced. However, increased intradialytic weight gain (IDWG) has been described as the side effect of this method. The aim of this study was to evaluate the effects of linear and stepwise sodium and UF profile on Intradialytic hypotension and IDWG.Materials and methods: This was a clinical trial study and crossover design. Twenty- six stable HD patients from two dialysis centers (Ali Asghar and Alzahra Hospitals) of Esfahan University underwent three treatments: (1) control, constant dialysate sodium concentration of 138 mmol/l with constant UF; (2) linear sodium profile + UF profile (type1), a linearly decrease dialysate sodium concentration (146–138mmol/l) combination with a linearly decrease UF rate. (3) Stepwise sodium profile + UF profile (type2), a stepwise decrease dialysate sodium concentration (146-138 mmol/l) combination with a stepwise decrease UF rate. Data were analyzed using χ2 and independent t-test in SPSS software.Results: In this study, a total of 26 patients (14 men, and 12 females) participated. The mean age was 46/819 years. In each group, 78 dialysis sessions and a total of 234 dialysis sessions were analyzed. The incidence of intradialytic hypotension, while receiving an intervention, was significantly reduced during linear and stepwise profiles, as compared with control (P<0.05, respectively). However, there was no significant differences between profiles. IDWG did not show any changes during three group.Conclusion: Sodium profile and UF profile modulates the dialysate sodium concentration and ultra filtration rate and also, prevents the incidence of IDH while reducing nursing intervention, without increasing IDWG. Thus, using sodium profile and UF profile groups (linear and stepwise) is recommended for the prevention of hypotension, as compared to routine method.Key words: J Mazand Univ Med Sci 2009; 19(72): 19-26 (Persian).